Gender and Sexuality in the North American Borderlands, 1492–1848 - Little, Ann M. (History compass, 2009)
Borderlands history has traditionally been dominated by the masculine concerns of warfare, politics, and diplomacy, but in the past two decades, women’s and gender historians have produced studies that reveal that gender and sexuality were central to all colonial North American borderlands encounters among and between Native Americans and Europeans. This new scholarship argues not just for the importance of women in borderlands societies, but for the importance of looking at gender identities, work roles, and sexual and marriage practices, and the role all of these things played in intercultural contact and conflict. Scholars interested in gender and sexuality should take a broadly comparative approach in this field, because of the striking similarities as well as important differences that emerge with a continental perspective.